Food and drug administration's critical path initiative and innovations in drug development paradigm: Challenges, progress, and controversies - Rajiv Mahajan; Kapil Gupta (Wolters Kluwer Medknow Publications, 2010)
During the last decade, despite increased investment in drug research and development related activity, stagnation in new drug discovery has been documented. Despite a 70% increase in investment in research and development-related activities, a 40% fall in launch of new chemical entities was seen during 1994-2004. A steep rise in the attrition rate of drug development has complicated the matter. Rising cost and increased attrition rates proved major barriers to investment in higher risk drugs or in therapies for uncommon diseases or diseases that predominantly afflict the poor. This prompted Food and Drug Administration (FDA) to highlight this problem in a 2004 white paper classified as "Critical Path Initiative" (CPI) and to initiate steps to target stagnation and rise in attrition rates. Many new drug development projects have started worldwide taking cue from CPI; adopting microdosing, adaptive designs and taking advantage of newly developed biomarkers under the CPI. This review discusses the various strategies adopted under CPI to decrease attrition rate and stagnation of new drug development, and the challenges and controversies associated with CPI.